(untitled) (Global Journal of Medical Research, 2014)
A 41 year old welder presented with the hook of a metallic spring impacted in the right medial and upper part of the orbit after being hit accidentally while working on a motorcycle. An orbital x-ray was done to determine the orientation and location of the hook of the metallic spring. The metallic spring was removed as guided by the radiographic image. Plain radiography proved helpful in forming a scheme for the management of this patient.